2014
DOI: 10.1530/rep-14-0230
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian steroids do not affect bovine endometrial cytokine or chemokine responses to Escherichia coli or LPS in vitro

Abstract: The risk of bacterial infection of the endometrium causing uterine disease in cattle is increased in the progesterone-dominated luteal phase of the ovarian cycle, while oestrogens or oestrus are therapeutic or protective against disease. The first line of defence against bacteria, such as Escherichia coli that cause inflammation of the endometrium, is the innate immune system, which recognises bacterial lipopolysaccharide (LPS). This study tested the hypothesis that cyclic variation in ovarian hormone concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 58 publications
4
44
1
4
Order By: Relevance
“…Furthermore, culturing cells for several days likely modulates steroid receptor expression and physiological function, although the same model of polarized bovine endometrial epithelial cells do secrete prostaglandins as expected [24]. The present study also supports the recent findings that stage of VECTORIAL IL6 FROM ENDOMETRIAL EPITHELIUM estrous cycle, exogenous steroids, or inhibitors for the steroid nuclear receptors did not affect IL6 secretion from conventional bovine endometrial epithelial or stromal cell cultures [38]. In mice, stage of estrous cycle also had little impact on the predominant apical secretion of IL6 from polarized epithelial cells, although exogenous estradiol reduced IL6 release [25].…”
Section: Vectorial Il6 From Endometrial Epitheliumsupporting
confidence: 88%
See 3 more Smart Citations
“…Furthermore, culturing cells for several days likely modulates steroid receptor expression and physiological function, although the same model of polarized bovine endometrial epithelial cells do secrete prostaglandins as expected [24]. The present study also supports the recent findings that stage of VECTORIAL IL6 FROM ENDOMETRIAL EPITHELIUM estrous cycle, exogenous steroids, or inhibitors for the steroid nuclear receptors did not affect IL6 secretion from conventional bovine endometrial epithelial or stromal cell cultures [38]. In mice, stage of estrous cycle also had little impact on the predominant apical secretion of IL6 from polarized epithelial cells, although exogenous estradiol reduced IL6 release [25].…”
Section: Vectorial Il6 From Endometrial Epitheliumsupporting
confidence: 88%
“…In the present study, exogenous progesterone, estradiol, or a combination of the steroids had little effect on TER or on IL6 secretion, although inflammation was suppressed by dexamethasone as expected [38]. However, caution is required when comparing the in vitro data from the present study with the in vivo situation.…”
Section: Vectorial Il6 From Endometrial Epitheliumsupporting
confidence: 44%
See 2 more Smart Citations
“…Lipopolysaccharide (LPS), produced by E. coli , a common causative agent of uterine infections in dairy cows, binds to TLR4 on uterine epithelial cells. This induces a pro‐inflammatory cascade of cytokines leading to altered prostaglandin (PG) production (increased PGE‐2:PGF2α ratio) by the uterus (Davies et al., ; Sheldon et al., ) which causes delayed luteolysis and extended cycles in animals with uterine infections (Davies et al., ; Saut, Healey, Borges, & Sheldon, ; Sheldon et al., ). In other studies, it was shown that LPS concentrations in peripheral blood (Mateus, Lopes da Costa, Diniz, & Ziecik, ), and within the ovarian follicular fluid (Herath et al., ), are elevated in animals with uterine infections, suggesting that LPS may also have direct effects on ovarian function.…”
Section: Introductionmentioning
confidence: 99%